2017
DOI: 10.1021/acs.jpcc.7b04434
|View full text |Cite
|
Sign up to set email alerts
|

PtRu Alloy Nanoparticles I. Physicochemical Characterizations of Structures Formed as a Function of the Type of Deposition and Their Evolutions on Annealing

Abstract: We have physicochemically characterized the formation of PtRu nanoparticles, deposited by evaporation onto highly oriented pyrolytic graphite, using in situ X-ray photoelectron spectroscopy, ex situ high-angle annular dark-field/scanning transmission electron microscopy, electron energy loss spectroscopy, and time-of-flight secondary ion mass spectrometry. We used three different orders of metal deposition: Pt evaporated onto Ru, Ru evaporated onto Pt and both metals evaporated simultaneously, and then followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
(105 reference statements)
3
14
0
Order By: Relevance
“…As in our previous Ru study on HOPG, the metals do not wet the carbon paper, causing the deposit to retract and form NPs. In addition, TOF-SIMS, high-angle annular dark-field scanning transmission electron microscopy (HAADF/STEM), and electron energy loss spectroscopy (EELS) on PtRu NPs showed that all the samples begin to form alloys on deposition, due to the high heats of condensation of Pt and Ru (∼5 and ∼6 eV, respectively). In both photomicrographs, many NPs are in contact because of their high number density.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As in our previous Ru study on HOPG, the metals do not wet the carbon paper, causing the deposit to retract and form NPs. In addition, TOF-SIMS, high-angle annular dark-field scanning transmission electron microscopy (HAADF/STEM), and electron energy loss spectroscopy (EELS) on PtRu NPs showed that all the samples begin to form alloys on deposition, due to the high heats of condensation of Pt and Ru (∼5 and ∼6 eV, respectively). In both photomicrographs, many NPs are in contact because of their high number density.…”
Section: Resultsmentioning
confidence: 99%
“…(Whether or not the anodic peak, seen during the reverse scan, is related to the removal of incompletely oxidized carbonaceous species is still debatable. 2,17−22 ) Although the value of the ratio for annealed deposit 2 is higher than that for the unannealed deposit, its peak areas are much smaller (Figure 3a,b and Table 1), and XPS 12 reveals that annealing has resulted in the deposition of surface hydrocarbon. This deposit may block active catalytic sites on the NP surface.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…H 2 /Ar) might induce Pt-nanoclusters to appear on the surface of the PtRu alloy NPs. 60 The electronic structure of the surface Ptatoms is changed by neighbouring Ru-atoms, which weakens the hydrogen adsorption energy. 19,61,62 Density functional (DFT) calculations of metal surfaces show synergistic effects (strain and ligand effects) when adjacent M-atoms are present alongside Pt-atoms.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%